Understanding Smart Environment: A Systematic Literature Review - Ardhana, Sonia Frisca Putri; Prasetyo, Yuli Adam; Mukti, Iqbal Yulizar; Abdurrahman, Lukman (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
In the rapidly evolving era of technological advancements, the concept of a Smart Environment emerges as a pivotal innovation in addressing the complex challenges of environmental sustainability. This study aims to provide a comprehensive evaluation of the Smart Environment's effectiveness in meeting urban community needs, while elucidating the synergy between business functions and the technological frameworks that drive the development of such environments. Utilizing a Systematic Literature Review (SLR) methodology, this research explores the terminologies, models, and technologies integral to the Smart Environment, focusing on their practical applications in sectors such as energy management, transportation, and natural resource conservation. The findings highlight the crucial role of the Internet of Things (IoT) in enhancing efficiency and sustainability, alongside the importance of robust data security and interoperability standards. This study not only contributes to a deeper understanding of the Smart Environment's impact on urban life but also serves as a valuable resource for future research, providing insights into the integration of societal needs with technological advancements to create sustainable, efficient, and intelligent urban environments.